A Review : The Effect of Nanoparticles in Vegetable Oil on Surface Roughness in Machining Processes - Pratiwi, Ayu; Noviyanto, Alfian (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2026)
The use of mineral oil based and synthetic coolants in machining processes remains dominant, despite their negative impacts on the environment and occupational health. Vegetable oils have emerged as an environment friendly alternative due to their biodegradable, non toxic properties, and renewable sources. However, thermal and tribological limitations restrict their performance under extreme conditions. To address this, various studies have investigated the addition of nanoparticles to vegetable oils to form nanofluids with improved lubrication and cooling performance. Nanoparticles such as aluminum oxide (Al₂O₃), molybdenum disulfide (MoS₂), and graphene have been shown to enhance thermal conductivity, reduce friction, and form protective tribological layers. This literature review discusses the effect of the combination of vegetable oil and nanoparticles on surface roughness in machining processes. The results show that nanofluids can significantly reduce surface roughness, particularly in Minimum Quantity Lubrication (MQL) systems. The effectiveness of nanofluids is greatly influenced by the type, size, and concentration of nanoparticles, where the optimal concentration varies but remains within a certain range (e.g., 2.5% for Al₂O₃). This study emphasizes that the development of plant-based nanofluids is a strategic approach toward efficient, environment friendly, and sustainable machining.